Prioritizing conservation actions for Pacific salmon in Canada. Issue 9 (20th May 2020) - Walsh, Jessica C.; Connors, Katrina; Hertz, Eric; Kehoe, Laura; Martin, Tara G.; Connors, Brendan; Bradford, Michael J.; Freshwater, Cameron; Frid, Alejandro; Halverson, Jessica; Moore, Jonathan W.; Price, Michael H. H.; et al.
Abstract: Current investment in conservation is insufficient to adequately protect and recover all ecosystems and species. The challenge of allocating limited funds is acute for Pacific salmon Oncorhynchus spp. in Canada, which lack a strategic approach to ensure that resources are spent on actions most likely to cost‐effectively recover diminished populations. We applied the Priority Threat Management framework to prioritize strategies most likely to maximize the number of thriving Pacific salmon populations on the Central Coast of British Columbia, Canada. These included 79 genetically, ecologically and spatially distinct population groups called conservation units (CUs) for five salmon species. This region has high salmon biodiversity and spans the territories of four First Nations: the Heiltsuk, Nuxalk, Kitasoo/Xai'xais and Wuikinuxv. Using structured expert elicitation of Indigenous and other experts, we quantified the estimated benefits, costs and feasibility of implementing 10 strategies. Under a business‐as‐usual scenario (i.e. no additional investments in salmon conservation or management), experts predicted that only one in four CUs would have >50% chance of achieving a thriving status within 20 years. Limiting future industrial development in salmon habitats, which was predicted to safeguard CUs from future declines, was identified as the most cost‐effective strategy. Investment in three strategies: (a) removal of artificial barriers to fish migration, (b) watershed protection and (c) stream restoration—at 11.3M CAD per year—was predicted to result in nearly half (34 of 79) of the CUs having a >60% chance of meeting the conservation objective. If all conservation strategies were implemented, experts estimated a >50% probability of achieving a thriving status for 78 of 79 CUs, at an annual cost of 17.3M CAD. However, even with the implementation of all strategies, most sockeye salmon CUs were unlikely to achieve higher probability targets of reaching the objective. Policy implications . We illustrate how Priority Threat Management can incorporate the perspectives and expertise of Indigenous peoples and other experts to prioritize conservation strategies based on their cost, benefit and feasibility. Implementation of this framework can help safeguard and recover Pacific salmon in Canada, and could also be used to prioritize actions for other conservation issues globally. Abstract : We illustrate how Priority Threat Management can incorporate the perspectives and expertise of Indigenous peoples and other experts to prioritize conservation strategies based on their cost, benefit and feasibility. Implementation of this framework can help safeguard and recover Pacific salmon in Canada, and could also be used to prioritize actions for other conservation issues globally.